2013
DOI: 10.1111/j.2047-2927.2013.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation in spermatozoa as a prospective marker in andrology

Abstract: Clinics of M€ unster, M€ unster, Germany SUMMARYRecent studies have shown associations of aberrant DNA methylation in spermatozoa with idiopathic infertility. The analysis of DNA methylation of specific genes could therefore serve as a valuable diagnostic marker in clinical andrology. For this purpose, rapid and reliable detection methods, reference values and the temporal stability of spermatozoal DNA methylation need to be established and demonstrated. In this prospective study, swim-up purified semen sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 55 publications
(90 reference statements)
2
47
0
Order By: Relevance
“…However, DNMT1 heterozygous mice had a normal reproductive ability, thus suggesting that DNMT1 in the heterozygous state is sufficient to maintain the required DNA methylation pattern (30,75,76). DNMT3a expression in the testis is upregulated prior to birth and during early postnatal life, whereas DNMT3b expression is downregulated during embryonic development and upregulated postnatally (15)(16)(17)(18)(19)(20). Notably, mice lacking DNMT3L have smaller testes, and a negligible number of spermatozoa by adulthood, resulting in sterile animals.…”
Section: Dna Methylation and Spermatogenesismentioning
confidence: 98%
See 2 more Smart Citations
“…However, DNMT1 heterozygous mice had a normal reproductive ability, thus suggesting that DNMT1 in the heterozygous state is sufficient to maintain the required DNA methylation pattern (30,75,76). DNMT3a expression in the testis is upregulated prior to birth and during early postnatal life, whereas DNMT3b expression is downregulated during embryonic development and upregulated postnatally (15)(16)(17)(18)(19)(20). Notably, mice lacking DNMT3L have smaller testes, and a negligible number of spermatozoa by adulthood, resulting in sterile animals.…”
Section: Dna Methylation and Spermatogenesismentioning
confidence: 98%
“…The methylation of constitutive heterochromatic and promoter regions is generally associated with reduced gene transcription (Fig. 1A) (15)(16)(17)(18). Therefore, DNA methylation is a type of epigenetic modification that can effectively promote gene silencing (Fig.…”
Section: Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach can be implemented in geographically distant laboratories, eliminating the problems associated with biological sample transportation. Our procedure allows repeated testing over an extended time-span of many years following sample collection, especially because it has been demonstrated that methylation of sperm DNA is not subject to change over time (14). Since assisted fertilization techniques have increasingly shown problems arising after a significant time-span (15), it becomes increasingly important to monitor the methylation status of germ cell genes.…”
Section: Resultsmentioning
confidence: 99%
“…MEST hypermethylation has repeatedly been linked to low sperm count, low progressive sperm motility and poor sperm morphology [8,61]. MEST is a candidate gene for the developmental disorder Silver-Russell Syndrome (SRS).…”
Section: Dna Methylation In Sperm Function and Male Infertilitymentioning
confidence: 99%